Political Behavior of Tirana Electorate - Lami, Roland (Italian Sociological Review, 2015)
In this study, ideological confusion is focuses mainly on the interdependence reated between the “deeply-social” factors of and political discourse. This analysis focuses on the empirical investigation regarding the perception of Tirana electorate for the relation between the political party structure and ideology, and between electorate and ideology. Based on the survey data, it results that very few people match the profile of a person who can make the distinction between principles of the Left and the Right. The majority of respondents fail to make this distinction or make this distinction but they vote pragmatically. Studies conducted in many countries with consolidated democracy show that both alternatives are possible. So there are several theories explaining the voting behavior, which can help us to understand the survey results and possible factors which affect this voting behavior.: ideology, political parties, voting behavior